The role of silver in the crystal structure of pyrargyrite: single crystal X-ray diffraction study - Laufek,F.; Sejkora,J.; Dusek,M. (Journal of Geosciences, 2010)
The crystal structure of pyrargyrite, Ag3SbS3, from Pribram-Haje (Czech Republic) was refined from single-crystal X-ray diffraction data in the space group R3c to an R factor of 0.0112. Unit-cell parameters are a = 11.0464(3) Å, c = 8.7211(2) Å, V = 921.60(4) Å3, Z = 6. In order to mimic the spread of electron density of silver, the non-harmonic Gram-Charlier development of the silver atomic displacement parameters was applied. A reasonable triangular shape of the electron density maximum centred in Ag position was obtained. The analysis of potential barriers between Ag sites reveals that silver transfer is equally probable via additional P site not only within the Ag-S-Ag spirals and Ag-Ag chains, but also between these spirals and chains.
Keywords: pyrargyrite; crystal structure; non-harmonic refinement; Ag diffusion; atomic displacement parameters